Analysis of Students' Ability to Understand The Concept of Compositional Function - Dwika Saputri; Reni Wahyuni; Raman Kumar (EDUPEDIA Publisher, 2026)
Purpose – This study aims to analyze students' ability to understand the concept of compositional functions based on indicators of understanding mathematical concepts. Understanding concepts is important in learning composition functions because students not only need to be able to do calculations, but also understand and apply concepts appropriately. Methodology – This study uses a qualitative approach with a qualitative descriptive research type. The research subjects consisted of six grade XI students at one of the Vocational High Schools (SMK) in Pekanbaru City in the even semester of the 2025/2026 school year. Subjects were selected using purposive sampling based on the results of the concept comprehension test. Data were collected through a description test consisting of two questions of composition function material. Data analysis is carried out based on two indicators of concept understanding, namely applying concepts algorithmically and presenting concepts in various mathematical representations. The percentage of achievement of each indicator is calculated based on the number of students who meet the indicators. Findings – The results of the study show that students' abilities are in the high category. The indicator applied concepts algorithmically reached a percentage of 83.33%, while the indicator presented concepts in various mathematical representations reached 100%. However, errors are still found in the application of composition procedures, especially in the process of function substitution. Novelty – This study provides an overview of the ability to understand the concept of composition function based on two indicators specifically in vocational school students. Significance – The results of the research can be an input for teachers in designing learning that emphasizes understanding of concepts, procedural accuracy, and the use of various mathematical representations.